Assessment of critical risk and success factors in construction supply chain: a case of Pakistan. Issue 12 (10th September 2022) - Abas, Muhammad; Khattak, Sikandar Bilal; Habib, Tufail; Nadir, Uroosa
Abstract: Assessment of critical risk and success factors is essential for successful execution of construction projects. This paper aims to identify the critical risk and success factors that affect the performance of the supply chain in the construction projects of Pakistan. For this purpose, a methodology was developed to identify risk and success factors. A questionnaire was designed to obtain the opinions of contracting companies, consulting firms, and project managers. Data were collected from 259 respondents and were analyzed statistically. The results of this study identified the top five critical risk factors that were prioritized based on the severity index. The most critical risk factors identified were, funding with a highest percentage of 93.89%, followed by shortage of material/equipment, cash flow, and bad weather. Among success factors, the communication has the highest severity index of 93.23%, followed by trust with a supplier, risk allocation, problem-solving, and joint working. These factors were discussed with implications that affect and impact the performance of the construction industry. The findings of this research can be used to guide the improvements in the construction industry in Pakistan, and other terror hit countries.